Essential Oils as Alternative Green Broad-Spectrum Biocides - Fulga Tanasă; Marioara Nechifor; Carmen-Alice Teacă (Plants)
Natural compounds from plants represent suitable options to replace synthetic biocides when employed against microorganisms in various applications. Essential oils (EOs) have attracted increased interest due to their biocompatible and rather innocuous nature, and complex biological activity (fungicide, biocide and anti-inflammatory, antioxidant, immunomodulatory action, etc.). EOs are complex mixtures of derived metabolites with high volatility obtained from various vegetal parts and employed to a great extent in different healthcare (natural cures, nutrition, phyto- and aromatherapy, spices) and cosmetics applications (perfumery, personal and beauty care), as well as in cleaning products, agriculture and pest control, food conservation and active packaging, or even for restauration and preservation of cultural artifacts. EOs can act in synergy with other compounds, organic and synthetic as well, when employed in different complex formulations. This review will illustrate the employment of EOs in different applications based on some of the most recent reports in a systematic and comprehensive, though not exhaustive, manner. Some critical assessments will also be included, as well as some perspectives in this regard.